(1101) The Experience of Socialist Countries (Especially of Czechoslovakia with Monetary Planning from Aspect of Savings تجربة الدول الاشتراكية (وخاصة تشيكوسلوفاكيا) مع التخطيط النقدي من منظور المدخرات - Ing. Petrivalsky. (INP., 2018)
All the socialist countries have gained a lot of experience in monetary planning and to a certain degree in planning of savings. at the same account there are some specific features of the development in monetary sphere and especially of savings. this is also the case of Czechoslovakia.